PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VI MATERI PENJAJAHAN BANGSA BARAT DI INDONESIA DALAM PEMBELAJARAN IPS (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' critical thinking abilities are greatly enhanced by Social Studies (IPS) education in elementary schools, particularly when it comes to comprehending historical occurrences like Western colonization in Indonesia. However, critical thinking abilities have not fully developed because IPS instruction is still mostly teacher-centered and does not adequately connect the course material to students' real-life experiences. A learning model like the Contextual Teaching and Learning (CTL) paradigm is required to make the connection between the course material and students' real-world experiences. Finding out how the CTL learning paradigm might improve sixth-grade students' critical thinking abilities while they study Western colonization in Indonesia is the aim of this study. A literature review that looks at numerous pertinent scientific publications is the methodology employed. It has been demonstrated that by actively including students in the contextual learning process, the CTL approach improves conceptual understanding, critical thinking abilities, and student engagement. As a result, the CTL model may be a useful substitute for raising the standard of social studies instruction in elementary schools, especially with regard to the growth of pupils' critical thinking abilities.